«ONE OF THE MOST HONOURED WORKERS ON THE FILD OF UKRAINE»: BODYANSKY OSIP IN ESTIMATION OF IVAN FRANKO - Pylypchuk, S. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article offers an analysis of Franko's evaluation of Osyp Bodyanskyi's scholarly and literary legacy. It has been indicated that Franko highly appreciated the renowned Slavist's contribution to literary studies. Focus is drawn to the scrupulous approach of Lviv scholar to the reception of Bodianskyi's "Naski ukrayinski kazky zaporozhtsia Iska Materynky" ("Our Ukiranian Tales by Isko Materynka, the Zaporozhian Cossack").